Functional Significance of CD57 Expression on Human NK Cells and Relevance to Disease - Nielsen, Carolyn M.; White, Matthew J.; Goodier, Martin R.; Riley, Eleanor M. (Frontiers in Immunology, 2013)
Historically, human NK cells have been identified as CD3-CD56+CD16+/- lymphocytes. More recently it has been established that CD57 expression defines functionally discrete subpopulations of NK cells. On T cells, CD57 expression has been regarded as a marker of terminal differentiation and (perhaps wrongly) of anergy and senescence. Similarly, CD57 expression seems to identify the final stages of peripheral NK cell maturation; its expression increases with age and is associated with chronic infections, particularly human cytomegalovirus. However, CD57+ NK cells are highly cytotoxic and their presence seems to be beneficial in a number of non-communicable diseases. The purpose of this article is to review our current understanding of CD57 expression as a marker of NK cell function and disease prognosis, as well as to outline areas for further research.